Optimization of the Two-Wheel Patrol Turjawali Unit of the Sabhara Unit of the Ciamis Police to Prevent the Occurrence of Criminal Acts of Motor Vehicle Theft in Maintaining Kamtibmas - Pratama, Wira (Police Studies Review, 2024)
The high number of criminal acts committed in the area of Ciamis Regional Police is my background in conducting this research. In this connection the community should obtain a guarantee of security and create a feeling of protection. So this is related to less or not optimal implementation of preventive tasks, namely the implementation of patrols by the ciamis police station, which for this police station is more effective using two-wheeled patrols. The theories and concepts used in analyzing this research are POAC management elements theory, patrol concept, du wheel patrol concept, 6M management factors theory, crime prevention theory, and optimization concepts. Furthermore, this study uses a qualitative approach with field research methods. This research is located in the jurisdiction of the Ciamis Regional Police with a focus on the two-wheeled Patrol Unit Sabhara Ciamis Regional Police. This study uses data collection techniques, namely interviews, observation, and document review. This research resulted in findings namely implementation through three stages, namely the preparation phase, the implementation phase, the termination stage. In this case the implementation is influenced by internal and external factors where there are obstacles and there are those that support its implementation. Supporting factors such as the completeness of existing vehicles, the availability of equipment, while inhibiting factors such as the lack of personnel and others. The Turjawali Sabhara Unit Ciamis Police Unit Patrol has been carried out in accordance with the regulated procedures but the implementation has not been paid attention to in detail so there are still shortages. More detailed control and supervision is needed so that implementation is in accordance with the rules and Kamtibmas can be achieved.